A Primer for a Contemporary Occasionalist Metaphysics of Nature - Edward Moad, Omar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Primer for a Contemporary Occasionalist Metaphysics of Nature